Transformation of maize photosynthetic carbon in reconstructed soils - Lei, Na; Zhang, Jing; Sun, Zenghui; Mu, Xingmin (Frontiers in Environmental Science, 2025)
IntroductionThe gully erosion control and land construction project was a major land improvement project implemented by human beings to increase the cultivated land area and improve the quality of cultivated land, and the implementation of the project had a great intervention and influence on the carbon cycle.MethodsThe microcosm experiment was carried out to reveal carbon cycle process of maize photosynthetic carbon in reconstructed soils during gully reclamation using a14C continuous labeling technique. The experimental soil came from Nanniwan Town, Yan’an City.ResultsThe distribution ratios of photosynthetic carbon in plants, roots and reconstructed soils were 83.96%–85.19%, 9.47–10.55% and 5.49–5.62%, respectively. It was revealed that the renewal rates of the dissolved organic carbon (DOC), microbial biomass carbon (MBC) and soil organic carbon (SOC) in reconstructed soils were 6.72%–14.64%, 1.70%–7.67% and 0.73%–1.99%, respectively.DiscussionThe distribution and transformation of maize photosynthetic carbon had a greater impact on the changes in the DOC and MBC that SOC. It was found that the mineralization rate of maize photosynthetic carbon in reconstructed soils was higher than 0.6 μg/g·d after construction, but with the extension of cultivation time, it slowed down, the decreasing rate increased, and finally stabilized at about 0.15 μg/g·d.